How do constitution-making processes fail? The case of Chile's Constitutional Convention (2021-22) - García Huidobro, Luis Eugenio; Verdugo, Sergio (Cambridge University Press, 2024)
This introduction to the symposium 'How do Constitution-Making Processes Fail? The Case of Chile's Constitutional Convention (2021-22)' situates the project in the field of constitution-making,provides context regarding the Chilean case,summarizes some possible explanations for the failure,and describes how each article contributes to the symposium as a whole. © The Author(s),2023. Published by Cambridge University Press.
Keywords: Activation failures; Chilean Constitution; Constitution-making; Constitutional Convention; Constitutional Referendum; 56 Ciencias Jurídicas y Derecho; ODS 8 - Trabajo decente y crecimiento económico; ODS 16 - Paz, justicia e instituciones sólidas